2020
DOI: 10.1080/02813432.2020.1753347
|View full text |Cite
|
Sign up to set email alerts
|

Associations between lifestyle, erectile dysfunction and healthcare seeking: a population-based study

Abstract: Objective: To investigate associations between age, lifestyle and erectile dysfunction (ED) in the general population and to explore associations between age, lifestyle and contact with a general practitioner (GP) regarding ED. Design: Cross-sectional web-based questionnaire study. Setting: The general Danish population. Subjects: A randomly selected sample of 48,910 men aged 20 years and older. Main outcome measures: Prevalence of ED and probability of contacting a GP regarding ED. In logistic regression mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Studies examining lifestyle factors and GP contact regarding LUTS are limited. Several studies, however, have examined associations between lifestyle factors and GP contact regarding different symptoms [17,28,29], and the various results indicate that lifestyle factors affect the healthcare-seeking behavior differently according to different symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Studies examining lifestyle factors and GP contact regarding LUTS are limited. Several studies, however, have examined associations between lifestyle factors and GP contact regarding different symptoms [17,28,29], and the various results indicate that lifestyle factors affect the healthcare-seeking behavior differently according to different symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Paulsen et al conducted a study among nearly 50,000 Danish men and confirmed statistically significant relationships between the self-assessment of physical fitness and reported ED [33]. The worse the patients assessed their exercise tolerance, the more often they reported sexual dysfunction.…”
Section: Discussionmentioning
confidence: 89%
“…The incidence of UI was only slightly higher among patients with high ARM severity compared to those with low ARM severity. A Danish survey of the prevalence of UI in the general population revealed that 20.4% of Danish women aged 20–29 yr had UI [38] and UI was associated with high BMI and age. Stress-induced UI was the dominant type among younger women.…”
Section: Discussionmentioning
confidence: 99%